Identification of cerebrospinal fluid biomarker candidates for anti-N-methyl-D-aspartate receptor encephalitis: High-throughput proteomic investigation - Li, Yuchen; Yang, Keyu; Zhang, Fang; Wang, Jing; Shen, Huijun; Liu, Miaomiao; Guo, Junhong; Wang, Jie (Frontiers in Immunology, 2022)
Background： Although the diagnosis is mainly dependent on detection of anti-N-methyl-D-aspartate receptor (NMDAR) antibodies in cerebrospinal fluid (CSF) and / or serum, there was no direct correlations between anti-NMDAR antibody titers in CSF and disease severity and prognosis in anti-NMDAR encephalitis patients. Here, we aimed to extensively identify CSF biomarkers related to the occurrence, development and prognosis of anti-NMDAR encephalitis using a high-throughput proteomic approach. Methods： A CSF cytokine antibody array containing 80 cytokines and inflammatory mediators related to immune and inflammatory responses was applied to identify biomarker candidates in individual CSF samples from a well-characterized cohort comprising patients with anti-NMDAR encephalitis (n=6) and controls (n=6). Validation and specific detection were performed in an extended cohort consisting of anti-NMDAR encephalitis patients (n=13), controls (n=13) and viral encephalitis (n=13) by enzyme-linked immunosorbent assay (ELISA). Additionally, the levels of some inflammatory proteins in three groups in cohort 2 reported in the previous literatures that may be involved in the development of anti-NMDAR encephalitis were also tested by ELISA. Correlations between candidate biomarkers and clinical characteristics of anti-NMDAR encephalitis patients were analyzed. Results： Three differentially expressed cytokines and inflammatory mediators were screened from 80 cytokines array in cohort 1. And functional enrichment analysis results suggested that these differential expressed proteins were related to autophagy, immune/inflammatory responses, cell death and other processes. In cohort 2, the elevations of cellular inhibitor of apoptosis protein-1 (cIAP-1), macrophage colony-stimulating factor (MCSF), CXC chemokine ligand13 (CXCL13), and nucleotide binding oligomerization domain—like receptor protein 3 (NLRP3) in anti-NMDAR encephalitis were validated by ELISA. Linear regression revealed the levels of CSF CXCL13 and cIAP-1 were positively correlated with the highest modified Rankin scale (mRS) score in acute phase (p < 0.05). And the level of cIAP-1 was positively correlated with the anti-NMDAR Encephalitis One-Year Functional Status (NEOS) score (p < 0.05). Conclusion: These biomarkers show promise functions to evaluate severity or prognosis of anti-NMDAR encephalitis. And the biological processes of immune/inflammatory responses, altered levels of autophagy and tumor necrosis factor (TNF) signal pathway may involve in the pathophysiology of anti-NMDAR encephalitis to some extent.